1991
DOI: 10.2337/diab.40.5.574
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sorbinil, Dietary myo-Inositol Supplementation, and Insulin on Resolution of Neuroaxonal Dystrophy in Mesenteric Nerves of Streptozocin-Induced Diabetic Rats

Abstract: Previous studies indicate that experimental diabetic autonomic neuropathy can be largely prevented by initiating therapy at the onset of diabetes. More clinically relevant, however, is the ability of therapy to reverse established neuropathy produced by long-standing diabetes. We have examined the effect of selected therapies on established neuroaxonal dystrophy (NAD) in ileal mesenteric nerves, a rat model of diabetic autonomic neuropathy. Groups of 3-mo-old rats were made diabetic with streptozocin (STZ-D) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Because axonal degeneration of peripheral nerves is observed by 5 months after STZ injection in rat (25), the delayed MNCV of diabetic animals in this study may be due to the dysfunction of Schwann cells. Although the pathological examination revealed that human diabetic neuropathy is largely an axonal disease, the dysfunction of Schwann cells, which play an important role in maintenance of axonal caliber, perineurial blood-nerve barrier, and nerve regeneration, is one of the essential abnormalities in diabetic neuropathy (26).…”
Section: Discussionmentioning
confidence: 75%
“…Because axonal degeneration of peripheral nerves is observed by 5 months after STZ injection in rat (25), the delayed MNCV of diabetic animals in this study may be due to the dysfunction of Schwann cells. Although the pathological examination revealed that human diabetic neuropathy is largely an axonal disease, the dysfunction of Schwann cells, which play an important role in maintenance of axonal caliber, perineurial blood-nerve barrier, and nerve regeneration, is one of the essential abnormalities in diabetic neuropathy (26).…”
Section: Discussionmentioning
confidence: 75%
“…In a morphological study of the autonomic nervous system, Schmidt et al (18) showed amelioration of neuroaxonal dystrophy by early treatment of diabetic rats with insulin, by pancreatic islet transplant or by administration of the aldosereductase inhibitor sorbinyl, but not by dietary administration of myo-inositol. However, when these treatments were instituted later, after neuropathy was established, inhibition of progression was attained, but the parameters studied did not normalize (19). These findings are in agreement with our results since the changes in resting HR persisted while MAP and HR variability improved at 7 days and returned to baseline values after this time, indicating that timedependent changes of metabolic parameters due to hyperglycemia and insulinopenia, or decreases in cardiac adrenergic receptors (20) may be possible explanations for the opposite findings.…”
Section: Bd Schaan Et Almentioning
confidence: 99%
“…The diabetic BB-rat SCG treated with an ARI showed improvement of decreased myo-inositol content, Na + -K + -ATPase activity and muscarinic signal transduction Mackway et al, 1986). ND in the SMG and ileal mesenteric nerves of chronic STZ-diabetic rats showed significant amelioration with ARI treatment (Schmidt et al, 1989c(Schmidt et al, , 1991(Schmidt et al, , 1998. ARI normalized diabetes-induced changes in VIP and galanin immunoreactivity in the STZ-diabetic rat myenteric plexus (Belai et al, 1996a) and improved or prevented diabetes-induced decrease in heart rate variability and vagus nerve axonal atrophy (Nowak et al, 1995).…”
Section: The Polyol Pathwaymentioning
confidence: 98%